A novel link between chronic inflammation and humanin regulation in children - Zhao, Yunhan; Mäkitie, Outi; Laakso, Saila; Fedosova, Vera; Sävendahl, Lars; Zaman, Farasat (Frontiers in Endocrinology, 2024)
ObjectiveChildren with inflammatory bowel disease (IBD) often suffer from poor bone growth and impaired bone health. Humanin is a cytoprotective factor expressed in bone and other tissues and we hypothesized that humanin levels are suppressed in conditions of chronic inflammation. To address this, humanin levels were analyzed in serum samples from IBD patients and in ex vivo cultured human growth plate tissue specimens exposed to IBD serum or TNF alone.MethodsHumanin levels were measured by ELISA in serum from 40 children with IBD and 40 age-matched healthy controls. Growth plate specimens obtained from children undergoing epiphysiodesis surgery were cultured ex vivo for 48 hours while being exposed to IBD serum or TNF alone. The growth plate samples were then processed for immunohistochemistry staining for humanin, PCNA, SOX9 and TRAF2 expression. Dose-response effect of TNF was studied in the human chondrocytic cell line HCS-2/8. Ex vivo cultured fetal rat metatarsal bones were used to investigate the therapeutic effect of humanin.ResultsSerum humanin levels were significantly decreased in children with IBD compared to healthy controls. When human growth plate specimens were cultured with IBD serum, humanin expression was significantly suppressed in the growth plate cartilage. When cultured with TNF alone, the expression of humanin, PCNA, SOX9, and TRAF2 were all significantly decreased in the growth plate cartilage. Interestingly, treatment with the humanin analog HNG prevented TNF-induced bone growth impairment in cultured metatarsal bones.ConclusionOur data showing suppressed serum humanin levels in IBD children with poor bone health provides the first evidence for a potential link between chronic inflammation and humanin regulation. Such a link is further supported by the novel finding that serum from IBD patients suppressed humanin expression in ex vivo cultured human growth plates.